Pengaruh penggunaan model pembelajaran kooperatif tipe student facilitator and explaining terhadap pemahaman matematik peserta didik - Eva Mulyani (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2016)
This study aimed to determine the effect of cooperative learning model Student Facilitator and Explaining on students’ mathematical understanding. The population in this study were students in seventh-grade students in academic year 2012/2013. Two classes were randomly selected as the samples, one class become experiment treated by cooperative learning model Student Facilitator and Explaining and other class become control treated by direct instructional model. The research used instruments of mathematics comprehension test and questioners. Data were analyzed using two different test average. The results showed a positive effect of applying cooperative learning model Student Facilitator and Explaining to students’ mathematical understanding. There was a positive attitude of students towards learning using a cooperative model of Student Facilitator and Explaining.